2022
DOI: 10.1155/2022/4382999
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-325-3p Targets Human Epididymis Protein 4 to Relieve Right Ventricular Fibrosis in Rats with Pulmonary Arterial Hypertension

Abstract: Background. Pulmonary arterial hypertension (PAH) usually causes right ventricular dysfunction, which is closely related to cardiac fibrosis. But cardiac fibrosis mechanism remains unclear. Our purpose was to explore microRNA-325-3p (miR-325-3p)/human epididymis protein 4’s (HE4) role in the occurrence and development of right ventricular fibrosis in PAH. Methods. The right ventricular fibrosis model of rats with PAH was constructed, and miR-325-3p was overexpressed to explore miR-325-3p’s effect on myocardial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…PAH usually causes right ventricular dysfunction, which is closely associated with cardiac fibrosis. Increased expression of type I and III collagen and MMP2/9 in the PAH group, as reported by Tang et al (2022) suggested that PAH induced myocardial fibrosis in rats, whereas miR-325-3p overexpression attenuated myocardial fibrosis in PAH rats. In addition, dual-luciferase and bioinformatics reported that miR-325-3p exhibited binding sites to human epididymis protein 4 (HE4), and miR- 325-3p inhibited cardiac fibroblast fibrosis by targeting and regulating HE4.…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...supporting
confidence: 55%
“…PAH usually causes right ventricular dysfunction, which is closely associated with cardiac fibrosis. Increased expression of type I and III collagen and MMP2/9 in the PAH group, as reported by Tang et al (2022) suggested that PAH induced myocardial fibrosis in rats, whereas miR-325-3p overexpression attenuated myocardial fibrosis in PAH rats. In addition, dual-luciferase and bioinformatics reported that miR-325-3p exhibited binding sites to human epididymis protein 4 (HE4), and miR- 325-3p inhibited cardiac fibroblast fibrosis by targeting and regulating HE4.…”
Section: Regulation Of Tgf-β/smad Signaling Pathway By Ncrnas In Card...supporting
confidence: 55%
“…Hypoxia activates some growth factors; stimulates protein kinase C, the mitogen-activated protein kinase family and phosphatidylinositol 3-kinase (PI3K); and regulates PAFs proliferation [ 105 ]. The early proliferation of PAFs caused by acute hypoxia exposure relies on p38 mitogen-activated protein kinase (p38 MAPK), and HIF-1α is also a key transcription factor in the biochemical reaction of hypoxia [ 106 , 107 ].…”
Section: Adventitia Remodeling In Pulmonary Vascular Remodelingmentioning
confidence: 99%
“…MiRNAs are single stranded RNAs molecules about 22 nucleotides in length that can regulate gene expression at the post-transcriptional level and play a critical role in cardiac fibrosis, mainly including left ventricular fibrosis, right ventricular fibrosis and atrial fibrosis (Table 1 , Ref. [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]).…”
Section: Mirnas In Cardiac Fibrosismentioning
confidence: 99%